Social Transitions and Gender: Human Agency to Explain Change - Nocenzi, Mariella; Musolino, Santina (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
Gender studies are born and establish themselves as a particular perspective of reading social phenomena as a whole, but also as an area of study oriented towards the analysis and understanding of specific problems and objects of study (Antonelli, 2018). Thanks to their intrinsically dynamic nature, they have proved to be particularly sensitive to changes in an increasingly complex society and capable of adopting theoretical and methodological approaches aimed at promoting their understanding. An example above all, the adoption of the intersectional theoretical approach which, by analyzing the multiple dimensions of the person and the value they have in society, allows us to grasp the hierarchies, asymmetries and various forms of oppression that characterize the position social.